A Web‐Based Application for Initial Screening of Living Kidney Donors: Development, Implementation and Evaluation. Issue 2 (3rd December 2012) - Moore, D. R.; Feurer, I. D.; Zavala, E. Y.; Shaffer, D.; Karp, S.; Hoy, H.; Moore, D. E.
<x xml:space="preserve">Abstract</x> Most centers utilize phone or written surveys to screen candidates who self‐refer to be living kidney donors. To increase efficiency and reduce resource utilization, we developed a web‐based application to screen kidney donor candidates. The aim of this study was to evaluate the use of this web‐based application. Method and time of referral were tabulated and descriptive statistics summarized demographic characteristics. Time series analyses evaluated use over time. Between January 1, 2011 and March 31, 2012, 1200 candidates self‐referred to be living kidney donors at our center. Eight hundred one candidates (67%) completed the web‐based survey and 399 (33%) completed a phone survey. Thirty‐nine percent of donors accessed the application on nights and weekends. Postimplementation of the web‐based application, there was a statistically significant increase (p < 0.001) in the number of self‐referrals via the web‐based application as opposed to telephone contact. Also, there was a significant increase (p = 0.025) in the total number of self‐referrals post‐implementation from 61 to 116 per month. An interactive web‐based application is an effective strategy for the initial screening of donor candidates. The web‐based application increased the ability to interface with donors, process them efficiently and ultimately increased donor self‐referral at our center.